Knowledge, Attitudes, and Practices Regarding Dengue Prevention Among Health Volunteers in an Urban Area - Malang, Indonesia - Alidha Nur Rakhmani; Lilik Zuhriyah (Korean Society for Preventive Medicine, 2024)
Objectives: The dengue prevention program known as "One House One Mosquito Larva Inspector" involves health volunteers who play a crucial role in the surveillance of mosquito larvae and reporting their findings to local public health officials. This study aimed to identify factors related to the knowledge, attitudes, and practices (KAP) of dengue prevention behavior among these health volunteers. Methods: A study was conducted in 5 sub-districts in Malang, an urban area in Indonesia. We employed a cross-sectional design and utilized a semi-structured questionnaire to assess the KAP of 400 health volunteers. Data were collected through face-to-face interviews. Results: Multiple logistic regression analysis revealed that individuals with a more positive attitude (odds ratio [OR], 1.69; p<0.05) and those with family sizes greater than five persons (OR, 1.90; p<0.05) were more likely to engage in effective dengue prevention practices. Additionally, possesing good knowledge was significantly assocated with more positive attitude (OR, 2.24; p<0.001). Furthermore, 40% reduction in positive attitude was observed in those over 45 years (OR, 0.60; p<0.05). The best practices most frequently reported by the majority of respondents included always reporting their surveillance activities (75.8%) and cleaning the water container in the bathroom at least once a week (65.2%). However, only 52.2% of respondents regularly checked for mosquito larvae in their neighborhood. Conclusions: Sustainable promotion and training for the "One House One Mosquito Larva Inspector" initiative are necessary, particularly among young health volunteers, to improve dengue prevention behaviors both within their own homes and in the surrounding environment.